Efficient Catalytic Upgrade of Fructose to Alkyl Levulinates with Phenylpyridine-phosphotungstate Solid Hybrids - Fang, Chengjiang; Li, Yan; Yu, Zhaozhuo; Li, Hu; Yang, Song (Current Green Chemistry, 2019)
Biomass, as the most abundant and renewable organic carbon source, can be upgraded into various value-added platform molecules. To implement more sustainable and economic catalytic biomass valorization, reusable heterogeneous catalysts would be one of the preferable choices. In this work, a series of phosphotungstic acid-based solid hybrids were produced by assembly of phosphotungstic acid with different pyridines using a facile solvothermal method. The obtained 3- phenylpyridine-phosphotungstate hybrid displayed superior catalytic performance in the upgrade of fructose to methyl levulinate with 71.2% yield and 83.2% fructose conversion at 140 ºC for 8 h in methanol, a bio-based and environmentally friendly solvent, which was probably due to its relatively large pore size and high hydrophobicity. This low-cost and eco-friendly catalytic process could be simply operated in a single pot without cumbersome separation steps. In addition, the 3- phenylpyridine-phosphotungstate catalyst was able to be reused for four times with little deactivation.
Keywords: heterogeneous catalysis